Challenges and risks of using Omega-3 fatty acids in the supportive treatment of depression - Joanna Orzechowska; Michał Orzechowski; Paulina Fijałek; Jan Karczmarz; Aleksandra Paprocka; Marika Gutowska; Agnieszka Kosińska; Urszula Świrk; Wiktoria Belcarz; Karolina Kalinowska (Quality in Sport)
Introduction: Omega-3 fatty acids, including α-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), are essential nutrients with anti-inflammatory and neuroprotective properties. EPA has demonstrated potential in mitigating depression by enhancing neurotransmitter synthesis, including dopamine and serotonin. However, gastrointestinal side effects, fatigue, anxiety, contamination risks (e.g., mercury, lead), and variability in supplement quality and accessibility pose significant challenges. Addressing these issues is essential to optimize the safe and effective therapeutic use of omega-3 fatty acids in depression management.